Implementation of Ishikawa Diagrams Learning Model to Enhance Learning Outcomes of Grade V Students on Islamic Education Subject at Muhammadiyyah Elementary School Kedung Gudel - Dinil Fadhilah, Linda; Wanti Listia Ningsih, Anisa; Hasanah, Nia (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) Sekolah Tinggi Ilmu Tarbiyah Muhammadiyah Tempurrejo Ngawi, 2023)
This study aims to evaluate the implementation of the Ishikawa Diagrams Learning Model as an alternative teaching strategy to enhance the learning outcomes of Grade V students in the Islamic Skills Study (SKI) subject at Muhammadiyyah Elementary School Kedung Gudel. This learning model is based on constructivist learning theory, which emphasizes the active role of students in learning and the use of visual aids to facilitate concept understanding. The method used is Classroom Action Research (CAR), involving student participation in the learning process that includes problem analysis and solution formulation. The results show that the implementation of the Ishikawa Diagrams Learning Model significantly improves student learning outcomes in the SKI subject. By using Ishikawa diagrams, students can identify factors influencing their understanding of the material, such as lack of understanding of basic concepts or lack of learning motivation. Additionally, through discussion and collaboration in problem-based learning, students can develop a deeper understanding of the concepts taught. The implications of this research are that the Ishikawa Diagrams Learning Model can be an effective alternative in enhancing SKI learning at the elementary school level. By utilizing a constructivist approach and visual aids, teachers can create a learning environment that stimulates critical thinking and active student participation. Moreover, this research also highlights the importance of using teaching methods that align with the characteristics of students and the subject matter being taught.